(untitled) (SCIENCE TIME JOURNAL, 2025)
This study explores the impact of modern educational platforms on the teaching and learning of English as a Foreign Language (EFL). The research investigates the effectiveness of platforms such as Google Classroom, Moodle, Zoom, and Edmodo in enhancing language acquisition, learner engagement, and instructional efficiency. Findings show that technology-enhanced learning environments foster more interactive, personalized, and accessible EFL instruction.